The effect of soil conditioner and growth booster on the agronomic characters and number of nodules of black soybean - Turmuktini, Tien; Santoso, I Putu Rahmat; Amalia, Lia; Sondari, Nunung; Ria, Elly Roosma; Muliani, Yenny; Kantikowati, Endang; Simarmata, Tualar (Universitas Padjadjaran, 2025)
Soil Conditioner & Growth Booster (SCGB) is a potion that was made to be used as a soil conditioner and plant growth promoter. SCGB is made from organic matter, biological fertilizers, soil ameliorants, and microelements. This research aims to determine the best dosage of SCGB on the agronomic characters, effective nodules, and black soybean variety ‘Detam-1’ yield. This research was conducted in the experimental field of the Faculty of Agriculture, Winaya Mukti University, Sumedang, Indonesia. This experiment used a simple randomized block design (RBD) with six treatments (0, 3, 6, 9, 12, 15 kg/ha) and repeated 4 times. The observation was conducted on a number of effective root nodules, plant height, number of leaves, 100-grain weight, number of pods, seed weight per plant, and seed weight per plot. The result showed that SCGB application significantly improved agronomic characteristics of black soybean plants, increasing the number of effective nodules by 147% to 168% compared to untreated plants. A dose of 3 kg/ha SCGB showed the best results in increasing 35% on yield seed weight per hectare compared to without application of SCGB.